Procedures used for assessment of stuttering frequency and stuttering duration. (December 2013) - Jani, Leanne; Huckvale, Mark; Howell, Peter
Abstract: Frequency of stuttered syllables and their durations were assessed using different procedures. The experiment examined overall syllable counts, counts of stuttered syllables and measures of stutter durations when they were made simultaneously or successively. Samples of speech with associated syllable, stuttered syllable and duration measurements of stuttering events were employed in reference transcriptions. Samples contained a minimum of 200 syllables. Ten participants assessed these samples for syllables, stuttered syllables and duration in an experiment. The responses of these participants were stored in alignment with the speech recordings for analysis. Performance was significantly more accurate (relative to transcriptions) for measures other than duration when the successive procedure was used as opposed to the simultaneous procedure. Although the successive method was more accurate, accuracy of stutter event identification was low for most participants. The procedure that allowed listeners to replay a speech sample and count the syllables, stuttered syllables and durations in three passes yielded more accurate syllable and stuttered syllable counts than procedures that required these judgments to be made in one pass.